COMPREENSÕES SOBRE A VIDA ESCOLAR DOS ALUNOS COM ALTAS HABILIDADES/SUPERDOTAÇÃO REFERENTES À EDUCAÇÃO MATEMÁTICA . - FÁBIO PALÁCIO BATISTA (2022)
When we talk about school inclusion, we usually think of students with sensory limitations. We hardly remember students with high abilities or giftedness who, according to data from the 2020 school census, are 23,506 enrolled in Brazil. Of these, 350 are enrolled in Mato Grosso do Sul. Specifically in Campo Grande/MS, 192 are enrolled. Thus, this master's research in Mathematics Education aims to understand what happens after the identification of the student with high abilities or overdotation with affinities in Mathematics in the classroom inclusion, in the practices involving Mathematics Education. To achieve our goal, we conducted a narrative research based on semi-structured interviews with students who attend or have attended the Mathematics - undergraduate course and the State Center for Multidisciplinary Care for High Abilities/Super ability, which is responsible for identifying and monitoring these students in their school and life trajectory. We also interviewed members of the pedagogical team of the Center. We adopted the convergence analysis for the treatment of the data produced. The results showed that the identification of high abilities or overgiftedness causes changes in the school life of these students, such as a change in the feeling of exclusion in the classroom, brings a better understanding of teachers regarding certain behaviors presented, and helps in the development of pedagogical strategies for inclusion of these students in the classroom.